2020
DOI: 10.1073/pnas.1918307117
|View full text |Cite
|
Sign up to set email alerts
|

Combined inhibition of JAK/STAT pathway and lysine-specific demethylase 1 as a therapeutic strategy in CSF3R/CEBPA mutant acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) is a deadly hematologic malignancy with poor prognosis, particularly in the elderly. Even among individuals with favorable-risk disease, approximately half will relapse with conventional therapy. In this clinical circumstance, the determinants of relapse are unclear, and there are no therapeutic interventions that can prevent recurrent disease. Mutations in the transcription factor CEBPA are associated with favorable risk in AML. However, mutations in the growth factor rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 61 publications
2
25
0
Order By: Relevance
“…Another way in which the JAK-STAT pathway contributes to the pathogenesis of AML is the reliance of leukemic cells on its signaling. AML cells carrying CEBPA or CEBPA/CSF3R mutations are sensitive to the inhibition of the JAK-STAT pathway [97]. Similar sensitivity has been detected in AML cells expressing RUNX1-RUNX1T1 [98].…”
Section: Dysregulation Of Jak-stat Signaling In the Pathogenesis Of Amlsupporting
confidence: 53%
“…Another way in which the JAK-STAT pathway contributes to the pathogenesis of AML is the reliance of leukemic cells on its signaling. AML cells carrying CEBPA or CEBPA/CSF3R mutations are sensitive to the inhibition of the JAK-STAT pathway [97]. Similar sensitivity has been detected in AML cells expressing RUNX1-RUNX1T1 [98].…”
Section: Dysregulation Of Jak-stat Signaling In the Pathogenesis Of Amlsupporting
confidence: 53%
“…These results confirm that the drug combination produces greater cytotoxicity than either drug alone. In other molecular subtypes of AML, LSD1 inhibition promotes cell death through differentiation of immature AML blasts 13,[49][50][51][52][53] . Surface expression of the maturation associated marker, CD86, was increased by LSD1 inhibitor alone and to a similar degree when combined with avapritinib (Supplementary Figure 1 E-F).…”
Section: Characterization Of Synergistic Cytotoxicity Following Kit and Lsd1 Inhibitionmentioning
confidence: 99%
“…LSD1 also has the function of non-histone lysine methylation [ 113 ], which is not discussed here. In addition, many recent studies have shown that LSD1 can be an important molecular target for the treatment of acute myeloid leukemia [ 114 , 115 ], but therapies directly associated with HIFs activity need to be further explored.…”
Section: Epigenetic Regulation Of Hifs Activitymentioning
confidence: 99%